Pasar Tradisional Di Pekanbaru Dengan Pendekatan Arsitektur Tropis - Dede Novita; Ratna Amanati; Pedia Aldy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Traditional market is public facility that must be in every subdistrict. Base on data from Dinas Pasar Pekanbaru, until 2015 Pekanbaru traditional market that managed by government there are 6 units. There are Agus Salim market, Labuh Baru market, Simpang Baru market, Cik Puan market, Rumbai market and Lima Puluh market. Total subdistrict in Pekanbaru city is 12 subdistricts. Therefore Dinas Pasar Pekanbaru must be increase the quantity of traditional market in every subdistrict. It makes pasar kaget grow up. Therefore, Rumbai subdistrict highly require for traditional market. The concept of traditional market design is interaction with nature, building, and human. It’s mean, how to make every element in traditional market area interacting each other. The require of tropical architecture influence in traditional market design is differentiate this market with traditional market that must be exist before. Therefore the market that doing adaption with environment around building, whether nature or circumstance in around building. Design element of Pekanbaru traditional market with tropical architecture approachment is zoning, the mass order, the exterior order, mass form, the interior order, and structure. The concept is applied on mass form that follows the site and facilitate the access of visitors to reach the parking area into the buildings, and between buildings. The interaction is realized in the form of pedestrian bridge and the travellator. Keywords: Traditional Market, Interaction, and Tropical Architecture